A Zero-Trust Model-Based Framework For Managing Of Academic Dishonesty In Institutes Of Higher Learning - et. al., Atiff Abdalla Mahmoud Arabi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As Academic dishonesty has become one of the most disturbing problems in many Institutions of higher Learning (IHLs) across the globe [1],[2], it has been noticed that this behavior will lead to an unfair atmosphere of competition among the students[3]. As part of a larger study on academic dishonesty, this paper aims to explore the effective countermeasures towards academic dishonesty and propose a framework for the prevention of academic dishonesty in IHLs based on the Zero Trust Model. Furthermore, this work aims to address the gap in the prevention of academic dishonesty in IHLs by outlining the components of academic integrity. As result, this study seeks to provide an in-depth examination of universities' policy on academic integrity, identify cultural and technological shifts to academic integrity education policy, address faculty and student engagement in academic integrity initiatives, and identify priorities in preventing academic misconduct and promoting academic integrity. The main objective will be to develop a Zero Trust Model based framework for prevention of academic dishonesty.